Halal Certification and the National Treatment Principle: Challenges in Harmonizing Indonesian Regulations with the WTO - Salsabila Nur Fatikha (Faculty of Law Universitas Sebelas Maret, 2025)
This paper examines Indonesia’s mandatory halal certification policy under Law No. 33 of 2014 concerning Halal Product Assurance (UU JPH) and its implications within the framework of international trade law. The law requires all products, both domestic and imported, to obtain halal certification before entering the Indonesian market, aiming to safeguard the religious rights of Muslim consumers. However, as a domestic regulatory measure, this obligation may create unintended trade barriers, particularly for foreign producers, by imposing additional procedural and compliance burdens. This raises concerns about Indonesia's compliance with the World Trade Organization (WTO) principles, especially the national treatment obligation under the General Agreement on Tariffs and Trade (GATT) and the Technical Barriers to Trade (TBT) Agreement. The study highlights the legal and policy tension between protecting public morals and ensuring non-discrimination in global trade. It concludes by stressing the need for Indonesia to reconcile its domestic religious and consumer protection objectives with its international commitments, to avoid potential violations of WTO obligations and to promote a fair and equitable trade environment.